A systematic review of complications of attico-antral type of chronic suppurative otitis media in our region - Khadkekar, Shashin; Benny, Libin Mathew; Gujrathi, Atishkumar B.; Gadpayale, Nishikant; Paikrao, Yogesh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Chronic suppurative otitis media (CSOM) is a very common disease that should be carefully treated, as severe complications can develop. Despite the significantly decrease incidence of CSOM-related complications since the introduction of antibiotics, this clinical problem has not been eliminated. Methods: This was an observational study conducted including 60 cases of attico-antral type of CSOM and its complications. Detailed study of determinants of attico-antral type of CSOM and its complications were studied. The various options in the management of disease and its complications with their outcomes were studied. Results: Majority of study participants belonged to lower socio-economic group. intra-temporal complications were most common complications and most of the patients required canal wall down surgery. Majority patients had complete recovery of the disease without recurrence during 3 months of follow-up. Conclusions: Our study concluded majority of the patients belonged to the low socioeconomic status. It was also clear from the study that timely intervention in the form of early diagnosis and administration of proper treatment resulted in complete recovery of majority of patients.